Cloud Framework for the Networked Expert and Analytical Tools Integration - Ermakov, A.; Klimenko, S.; Merkulov, A.; Panfilov, S.; Raikov, A.N. (Trudy Instituta sistemnogo programmirovaniâ, 2018)
Information-analytical decision support systems in government and business are distributed. There are two substantially different approaches of information, experts and analytical support of decision-making. The first is based on using the information that is stored in electronic databases, and the second - analyzing of the experts’ views in real time. We propose a design solution for creating the cloud framework for integrates the heterogeneous information, experts and analytical tools in the cloud that provides the convergence of the decision-making processes. The processes can include network expertise, cognitive modeling, visualization and analysis of Big Data. Examples of practical testing of the individual components are shown.